Pajak Menurut Imâm Al-Juwayni, Studi Literatur Kitab Ghiyâthi Al-Umam Fi Iltiyats Al-Ẓulam - Bunyamin, Muhammad Taufik; Tanjung, Hendri; Ali, Mahbuby (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Maqâṣid Al-Shari’ah as part ofUṣûl Al-fiqh, is an inseparable tool of a personMujtahidin interaction with reality. There are pros and cons in Tax as an issue in Islamic economics as a product of ijtihad, Imâm Al-Haramayn discusses this comprehensively, because he differentiates betweenAl-Naṣ (Text),Tafsir Al-Naṣ, andTaṭbiq Al-naṣ (text application). The concept is outlined in detail in the discussion of Tax in the bookGhiyâṭi Al-umam Fi Iltiyath Al-ẓulam. This research aims to determine the concept of taxation contained in the book Ghiyâthi al-Umam, which is an example of applicationMaqâṣid al-Syari'ah according to Imam al-Juwaynî. This research uses a qualitative approach, namely Library Research;Library Research. This research is based on the literature of Imâm Al-ḥaramayn and his thoughts. This research uses Uṣûl Al-fiqh analysis and the derivation of its implementation, including Maqâṣid al-Syari'ah and Qawâid Fiqhiyah. Then as a comparison include Muqâranah al-Aqwâl Bayna al-Ulamâ al-Mu'tabarîn. The results of this research emphasize the need for a more basic understanding in understanding the context that develops within the Islamic Ummah,Maqâṣid Al-Shari’ah as a bridge between text and reality, it was used by Imâm Al-ḥaramayn, a pioneer of scienceMaqâṣid Al-Shari’ah. The concept of non-ideality within the Muslim community, especially in the context of the state, requires scholars to look for the most ideal ideas in understanding current developments without losing their solid footing. Taxes in their application as state income whose legitimacy is recognized by Islamic Sharia have pros and cons, these cons depart from the consensus regarding the respectability of wealth. In this case, Imâm Al-ḥaramayn proposed a pattern that is application-basedMaqâṣid Al-Shari’ah as a response to the tax polemic.